PHYSICAL DEVELOPMENT AND PUBERTY AMONG STUDENTS IN PRIMARY SCHOOL IN HOAN KIEM WARD, HANOI (Vietnam Journal of Community Medicine, 2026)
Objective: To describle the nutritional status and pubertal development among primary school students in Hoan Kiem ward, Hanoi in 2021.Medthods: Cross-sectional descriptive studyResults: This study was conducted on 2099 students in grades 1, 2, and 3, corresponding to children born in 2015, 2014, and 2013, at primary schools in Hoan Kiem ward, Hanoi, in October 2021. The results showed that the prevalence of overweight and obesity was 46%, while undernutrition accounted for 3,1%. All male students had normal pubertal development, whereas 84,7% of female students were within the normal range, 3,5% exhibited signs of precocious puberty, and 11,8% were undergoing puberty.Conclusion: The study indicated that the prevalence of physical growth disorders (overweight and obesity) among primary school students and the occurrence of early puberty in female students remain high and require further attention and management to ensure healthy growth and development in children.
Keywords: Physical development, puberty, primary school students.